2006
DOI: 10.1063/1.2168448
|View full text |Cite
|
Sign up to set email alerts
|

Direct identification of propargyl radical in combustion flames by vacuum ultraviolet photoionization mass spectrometry

Abstract: We have developed an effusive laser photodissociation radical source, aiming for the production of vibrationally relaxed radicals. Employing this radical source, we have measured the vacuum ultraviolet (VUV) photoionization efficiency (PIE) spectrum of the propargyl radical (C(3)H(3)) formed by the 193 nm excimer laser photodissociation of propargyl chloride in the energy range of 8.5-9.9 eV using high-resolution (energy bandwidth = 1 meV) multibunch synchrotron radiation. The VUV-PIE spectrum of C(3)H(3) thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…12 More recently, an experimental study employing vacuum ultraviolet photoionization mass spectrometry suggested the presence of vibrationally excited propargyl C 3 H 3 in a low pressure fuel/O 2 /Ar premixed flame. 13 Vibrationally excited species may also be found in fast flow reactors employed for kinetics studies. In some of these reactors, the radical is produced by photolysis of a molecular precursor.…”
Section: Introductionmentioning
confidence: 99%
“…12 More recently, an experimental study employing vacuum ultraviolet photoionization mass spectrometry suggested the presence of vibrationally excited propargyl C 3 H 3 in a low pressure fuel/O 2 /Ar premixed flame. 13 Vibrationally excited species may also be found in fast flow reactors employed for kinetics studies. In some of these reactors, the radical is produced by photolysis of a molecular precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high vacuum ultraviolet (VUV) energy resolution and the physics of photoionization, the ionization energies (IEs) of molecular species with different isomeric structures can readily be obtained by VUV photoionization efficiency (PIE) measurements [20]. Recently, flame-sampling photoionization mass spectrometry has been successfully applied for the identification of combustion species using broadly tunable synchrotron radiation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the photoionization spectra of many larger molecules, as well as a significant number of smaller ones, often show very little resonant autoionization structure. Interestingly, the high-resolution photoionization spectrum of the propargyl radical shows considerable intense structure converging to electronically excited states of the C 3 H 3 + cation. While the assignments of these resonances are currently tentative, their stability with respect to competing decay processes may be due to the relatively stiff structure of the radical, which could reduce the potential for radiationless transitions, or to the relative stability of the closed-shell propargyl C 3 H 3 + cation. The extent to which this resonance structure is preserved or modified in the more flexible radicals produced by the addition of a methyl rotor to the propargyl radical (HCC– • CH 2 ), depending on which H atom is substituted, is thus of some interest.…”
Section: Introductionmentioning
confidence: 99%